2010
DOI: 10.2174/156720210791184952
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside RB1 Reduces Neurologic Damage, is Anti-Apoptotic, and Down-Regulates p53 and BAX in Subarachnoid Hemorrhage

Abstract: Stroke is the second leading cause of death worldwide and the number one cause of adult disability in the United States and Europe. A subtype of stroke, subarachnoid hemorrhage (SAH), accounts for 7% of all strokes each year and claims one of the highest mortalities and morbidities. Many therapeutic interventions have been used to treat brain injury following SAH but none have reached the level of effectiveness needed to clinically reduce mortality. Ginsenoside Rb1 (GRb1), a major component of the Chinese trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Recently studies have shown that anti-apoptotic drugs ameliorate negative outcomes after SAH in animal models (Zhou et al, 2004; Zubkov et al, 2002). Current anti-apoptotic therapies for SAH focus on the MAPK pathway (Cahill et al, 2007; Suzuki et al, 2010b), the tumor suppressor p53 (Chen et al, 2011a; Li et al, 2010), and hypoxia inducible factor-1 (HIF-1) target genes. Additionally, intravenous mesenchymal stem cell administration in vivo provided neuroprotective effects by ameliorating neural cell apoptosis in SAH animal models (Khalili et al, 2012).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…Recently studies have shown that anti-apoptotic drugs ameliorate negative outcomes after SAH in animal models (Zhou et al, 2004; Zubkov et al, 2002). Current anti-apoptotic therapies for SAH focus on the MAPK pathway (Cahill et al, 2007; Suzuki et al, 2010b), the tumor suppressor p53 (Chen et al, 2011a; Li et al, 2010), and hypoxia inducible factor-1 (HIF-1) target genes. Additionally, intravenous mesenchymal stem cell administration in vivo provided neuroprotective effects by ameliorating neural cell apoptosis in SAH animal models (Khalili et al, 2012).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…The tumor suppressor gene, p53, also regulates apoptosis. In EBI after SAH, anti-apoptotic therapies have reported to ameliorate outcomes by targeting the MAPK pathway [62, 106, 114, 131], activating p53 [13, 16, 68, 76], and hypoxia inducible factor-1 (HIF-1) target genes by hyperbaric oxygen [84]. …”
Section: Experiments On Early Brain Injury After Sahmentioning
confidence: 99%
“…Li et al . [45] found that the ginsenoside Rb1 from P. ginseng relieves cerebral vasospasms and potentially protects against stroke and subarachnoid hemorrhaging and that the underlying mechanism may be partly related to the inhibition of the p53- and Bax-dependent proapoptosis pathways by Rb1. Jovanovski et al .…”
Section: Summary Of the Major Findings Of Selected Publicationsmentioning
confidence: 99%